THE JURIDICAL CONSEQUENCES OF CORPORAL PUNISHMENT BY TEACHERS AND PARENTAL LEGAL COMPLAINTS IN THE CONTEXT OF CHILD PROTECTION ACT - Muhammad Khoiru Royyan; Aulia Binta Emira; Sri Mulyati; Anindya Aryu Inayati (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study aims to analyze the juridical implications of the reporting of student guardians to teachers related to the practice of corporal punishment in the educational environment. This study is a normative legal research. The approach used is a legislative approach, which focuses on analyzing the applicable regulations. The primary legal source in this study is the Child Protection Law and Education policy. The data was analyzed using thematic analysis techniques. The results of the review show that the legal implication of the student's parents' reporting to the teacher is the blurring of the meaning of